How to diagnose equal opportunities between women and men in organizations - Amaia Lusa; Carme Martínez; Maria Dolors Calvet; Olga Pons; Marta Tura (Journal of Industrial Engineering and Management (JIEM), 2009)
Gender equality is now a matter that concerns all European countries. Despite the great effort made by governments and the progress of laws, gender discrimination still exists in family, social, cultural, political and economic spheres. Even today, it is rare to find women at the top level in companies. The path to equal opportunities is long and the only way to improve the situation is by means of appropriate equal opportunities plans. An essential part of the process of designing and implementing such action plans involves diagnosing the situation in a company. In this paper, an innovative indicator model is proposed. A review of numerous international private and public equal opportunities plans led to the design of a model to carry out a diagnose to identify all areas that could be corrected or improved by implementing specific measures, leading the company to deliver real equal opportunities policies. The indicator model is designed for the present historical context, though it is flexible enough to be adapted to each age and situation. The indicator model, which is original, will help companies carrying out one of the most important and essential parts of the process of designing and implementing and equal opportunities plan. Moreover, taking the indicator model companies ensure that all the relevant features are covered.
Keywords: 650; equal opportunities; gender mainstreaming; diagnose; management; human resources